Who withdraws? Psychological individual differences and employee withdrawal behaviors - Zimmerman, Ryan D; Swider, Brian W; Woo, Sang Eun; Allen, David G (Journal of applied psychology, 2016)
Psychological individual differences, such as personality, affectivity, and general mental ability, have been shown to predict numerous work-related behaviors. Although there is substantial research demonstrating relationships between psychological individual differences and withdrawal behaviors (i.e., lateness, absenteeism, and turnover), there is no integrative framework providing scholars and practitioners a guide for conceptualizing how, why, and under what circumstances we observe such relationships. In this integrative conceptual review we: (a) utilize the Cognitive-Affective Processing System framework (Mischel & Shoda, 1995) to provide an overarching theoretical basis for how psychological individual differences affect withdrawal behaviors; (b) create a theoretical model of the situated person that summarizes the existing empirical literature examining the effect of psychological differences on withdrawal behavior; and (c) identify future research opportunities based on our review and integrative framework.